Cerebrovascular disease and e-cigarettes use in adolescents and young adults: A critical concern for health professionals - Wong-intha, Pornpimon (Journal of Medicine and Health Sciences, 2025)
Cerebrovascular disease is a leading cause of mortality and vascular complications in the brain, significantly impacting public health systems worldwide, with a high number of patients and deaths per year. Smoking is a major risk factor in the development of the disease. Currently, electronic cigarettes (e-cigarettes) are gaining popularity among young people worldwide because of the misunderstanding that e-cigarettes are harmless. The liquid in e-cigarettes contains nicotine and many other harmful chemicals, such as aldehyde produced from vaporizing the liquid, which damages blood vessel walls, promotes atherosclerosis, affects the cardiovascular and neurological systems, and increases the risk of Cerebrovascular disease. This article reviews the effects of e-cigarettes on Cerebrovascular disease incidence in adolescents and young adults. This age groups exhibits the highest rate of e-cigarettes smoking and belief that they are safer than conventional cigarettes, alongside the insufficient regulations of e-cigarettes. Therefore, it is a challenge for health professionals to prevent stroke caused by e-cigarettes and reduce the use of e-cigarettes in adolescents and young adults by using evidence-based knowledge to provide health education to the public, particularly among adolescents and young adults. This includes developing guidelines for campaigns to prevent, reduce, and quit e-cigarettes use, monitoring social and public health impacts, and developing future research.